THE DISTINCTIVE FEATURES OF IMAM AL-TIRMIDHI’S WORK “SUNAN” (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the life, scholarly contributions, and distinctive methodological features of Imam Abu Isa Muhammad al-Tirmidhi (209–279 AH), one of the most eminent hadith scholars of the classical Islamic tradition. Special attention is given to his monumental compilation “Sunan al-Tirmidhi” (also known as “Al-Jamiʼ”), its various titles in the scholarly tradition, its unique technical terminology – including the categories of hasan, gharib, and hasan sahih – and its structural and jurisprudential characteristics. The study draws on primary Islamic scholarly sources and contextualizes Tirmidhi’s contribution within the broader history of hadith science and its integration with Islamic jurisprudence (fiqh).
Keywords: Imam al-Tirmidhi; hadith science; Sunan al-Tirmidhi; hasan; gharib; Islamic jurisprudence; Sihahi Sitta